Validation of the child and youth resilience measure among South African adolescents. - Kaymarlin Govender; Richard G Cowden; Kwaku Oppong Asante; Gavin George; Candice Reardon (PLoS ONE, 2017)
Resilience is a dynamic, interactive process between resources that contribute to safeguarding a person and the adversities they experience. Within this promotional framework of resilience, this study sought to validate the Child and Youth Resilience Measure (CYRM-28) among a sample of South African adolescents (N = 1854). Confirmatory factor analysis supported a superior level of fit for a 24-item, three-factor model (i.e., individual/social, familial, and community/spiritual). Internal consistency and test-retest reliability estimates at a 12-month interval (N = 648) supported the reliability of the scales. Higher scores on the scales were associated with feeling more connected at school, greater parental monitoring perceptions, and lower sexual risk, confirming the convergent and criterion validity of the instrument. Partial discriminative power was evidenced based on selected scale distinctions according to age and sex groupings. Collectively, the findings suggest the 24-item CYRM is a valid and reliable self-report measure to assess the availability of resources associated with resilience in South African youth.